Inovasi Layanan Jemput Bola (Eazy Passport) Oleh Kantor Imigrasi Surabaya: Strategi Peningkatan Aksesibilitas Layanan Keimigrasian - Ahmad Fitroni; Sri Kamariyah; Ika Devy Pramudiana; Dandy Patrija Wirawan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Access to fast, easy, and humane immigration services is a major challenge amidst the dynamics of urban community needs. The Surabaya Immigration Office responded to this condition through an innovative outreach service known as Eazy Passport. This innovation is designed to reach service users who have limited time and mobility. This study aims to evaluate the effectiveness of the Eazy Passport innovation in improving the accessibility of immigration services, using Parasuraman's service quality theory approach as an analytical framework. This type of research is descriptive qualitative. Data collection was conducted through in-depth interviews, field observations, and documentation of immigration officers and Eazy Passport service users. The main research instrument was the researcher himself who played an active role in the data extraction process. Data analysis used data reduction techniques, data presentation, and drawing conclusions according to the Miles and Huberman model. The results of the study showed that the five dimensions of Parasuraman's theory—tangibles, reliability, responsiveness, assurance, and empathy—have been optimally implemented in the Eazy Passport service. This service has been proven to shorten service time, increase public satisfaction, and expand the reach of services without adding excessive administrative burdens. The conclusion of this study states that the innovation of the jemput bola service has succeeded in becoming an effective strategy in improving the accessibility and quality of immigration services in Surabaya. Further research is suggested to use a quantitative approach or mixed methods to compare the effectiveness of conventional and jemput bola services in the context of different regions or institutions.